Mechanistic Investigations of Human Reticulocyte 15- and Platelet 12-Lipoxygenases with Arachidonic Acid - Wecksler, Aaron T. (2009)
Human reticulocyte 15-lipoxygenase-1 (15-hLO-1) and human platelet 12-lipoxygenase (12-hLO) have been implicated in a number of diseases, with differences in their relative activity potentially playing a central role. In the current paper, we characterize the catalytic mechanism of these two enzymes with arachidonic acid (AA) as the substrate. Using variable-temperature kinetic isotope effects (KIE) and solvent isotope effects (SIE), we demonstrate that both k(cat)/K(m) and k(cat) for 15-hLO-1 and 12-hLO involve multiple rate-limiting steps that include a solvent dependent step and hydrogen atom abstraction. Nevertheless, an unexpectedly low k(cat)/K(m) KIE was determined for 15-hLO-1 (KIE = 8), which increases to well above semi-classical predictions (KIE = 18) upon the addition of the allosteric effector molecule, 12-hydroxyeicosatetraenoic acid (12-HETE), indicating a tunneling mechanism. Furthermore, the addition of 12-HETE lowers the observed k(cat)/K(m) SIE from 2.2 to 1.4, indicating that the rate-limiting contribution from solvent rearrangement in the reaction mechanism of 15-hLO-1 has decreased, with a concomitant increase in the C-H abstraction contribution. Finally, the allosteric binding of 12-HETE to 15-hLO-1 decreases the K(m)(O(2)) for AA, but increases the K(m)(O(2)) for LA, such that the K(m)(O(2)) values become similar for both substrates (∼20 μM). Considering that the oxygen concentration in cancerous tissue can be below 5 μM, this result may have cellular implications with respect to the substrate specificity of 15-hLO-1.